Management / Theory and Practice: Fourth Edition - Cole G.A (Dp Publications Ltd, 1993)
This book aims to provide, in one concise volume, an introduction to the principal ideas and developments in the theory and practice of management as required by business and accountancy students. Preface, Glossary of Management Terms, Introduction to Management Theory, Classical Theories, Motivation and Leadership and Groups at Work, Systems Approaches to Management Theory, Management in Practice: Introduction, Planning, Organizing, Control in Management, Functional Management and Marketing and Production and Personnel and Financial, Marketing Management: Introduction, Production Management: Introduction, Personnel Management: Introduction, Financial Aspects of Management, Appendices, Index.